Food, Economic, and Livelihood Security of Farmers Under PMFBY in Kolar, Karnataka - Jiragal, Dr. Imrankhan; S, Dr. Ganesamoorthi; Mehnaj Khatoon; T. L, Dr. Mohan Kumar; C, Dr. Narayanaswamy (Indian Journal of Extension Education, 2025)
Indian agriculture faces multiple risks that threaten farmers livelihoods. The Pradhan Mantri Fasal Bima Yojana (PMFBY) was introduced to mitigate these risks through crop insurance. This study evaluates the impact of PMFBY on the food and economic security of farmers in Kolar district, Karnataka, during 2021–2022. A total of 200 farmers (150 beneficiaries, 50 non-beneficiaries) were surveyed across five taluks. Food and economic security were assessed using specific indicators. Findings indicate that PMFBY beneficiaries experienced slightly better livelihood security than non-beneficiaries. Beneficiaries prioritized year-round food access (mean: 4.63), while non-beneficiaries relied more on the adequacy of Public Distribution System (PDS) grains (mean: 4.48). Economic security was primarily associated with optimal resource utilization (beneficiaries: 4.61; non-beneficiaries: 4.52). Overall, 53.5% of beneficiaries reported improved food security and 57% experienced enhanced economic stability. The results suggest a modest positive impact of PMFBY on farmer resilience. However, challenges such as delayed insurance payouts and awareness gaps persist. Strengthening implementation, improving claim processing, and increasing outreach efforts could enhance the scheme’s effectiveness. Continuous evaluation is essential to optimize PMFBY’s role in promoting sustainable agricultural livelihoods.